If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7t + -3(1 + t) = -19 7t + (1 * -3 + t * -3) = -19 7t + (-3 + -3t) = -19 Reorder the terms: -3 + 7t + -3t = -19 Combine like terms: 7t + -3t = 4t -3 + 4t = -19 Solving -3 + 4t = -19 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4t = -19 + 3 Combine like terms: -3 + 3 = 0 0 + 4t = -19 + 3 4t = -19 + 3 Combine like terms: -19 + 3 = -16 4t = -16 Divide each side by '4'. t = -4 Simplifying t = -4
| 5/6(6)+1/2=2/3 | | 0.372= | | -12(-3x)=42 | | 2/4+3=8-2/4 | | ax+bx+12=4 | | 1540+x(145.50)=3140.50 | | 6(12x+2)=72x-10 | | 102/3*128/9 | | 1/5(10h+15)+5 | | -3x-8y=12 | | 4x-12y=48 | | 6+12/x=-1 | | 1/10x-5=65 | | 9(3y+40)= | | -4(2-3x)=2(3x-8)2x | | p/6+9+14 | | f(b)=b^2+7b+13 | | 520+x(5)=550 | | (25r^2-35r+10)/(5r-2) | | 85/4*9-17+5699/6*8-6+173 | | 3(y+2)-4(2y-1)=8 | | 80=5u-15 | | -8+1y=-9 | | 2x^2y+3xy^2=0 | | -8x-3y=12 | | 12=7-(p+4) | | -2x+4(-8)=-8 | | 12t-8t=-52solvet | | 85/4*9-17+56 | | 5n-5/3 | | .7p+4.6=7.3-.2 | | -11+6a=5+2a |